Chromosome-scale assemblies of S. malaccense, S. aqueum, S. jambos, and S. syzygioides provide insights into the evolution of Syzygium genomes - Ouadi, Sonia; Sierro, Nicolas; Kessler, Felix; Ivanov, Nikolai V. (Frontiers in Plant Science, 2023)
Syzygium is a large and diverse tree genus in the Myrtaceae family. Genome assemblies for clove (Syzygium aromaticum, 370 Mb) and sea apple (Syzygium grande, 405 Mb) provided the first insights into the genomic features and evolution of the Syzygium genus. Here, we present additional de novo chromosome-scale genome assemblies for Syzygium malaccense, Syzygium aqueum, Syzygium jambos, and Syzygium syzygioides. Genome profiling analyses show that S. malaccense, like S. aromaticum and S. grande, is diploid (2n = 2x = 22), while the S. aqueum, S. jambos, and S. syzygioides specimens are autotetraploid (2n = 4x = 44). The genome assemblies of S. malaccense (430 Mb), S. aqueum (392 Mb), S. jambos (426 Mb), and S. syzygioides (431 Mb) are highly complete (BUSCO scores of 98%). Comparative genomics analyses showed conserved organization of the 11 chromosomes with S. aromaticum and S. grande, and revealed species-specific evolutionary dynamics of the long terminal repeat retrotransposon elements belonging to the Gypsy and Copia lineages. This set of Syzygium genomes is a valuable resource for future structural and functional comparative genomic studies on Myrtaceae species.